In vitro antimicrobial screening of Manihot esculenta Sao Pedro Petro Extract and Identification of Active Compounds - Widiastuti, Diana; Sinaga, Siska Elisahbet; Sofian, Yayan; Mulyati, Ade Heri; Warnasih, Siti; Sadjarwa, Boedi; Dhiandani, Sri Boedi; Herlina, Eka; Triastinurmiatiningsih, Triastinurmiatiningsih; Agustine, Dine (Chimica et Natura Acta, 2024)
Sao Pedro Petro cassava tubers (Manihot esculenta Ctro) are one of the cassava varieties, generally cultivated in tropical and subtropical areas. This plant has the potential to contain antimicrobial bioactive compounds. This research aimed to demonstrate the antibacterial activity of each fraction and subsequently identify the specific active fraction for in-depth analysis of its bioactive compounds. The evaluation of antimicrobial activity and the identification of bioactive compounds were conducted using the well-diffusion method and UPLC-QTOF MS (Ultra Performance Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry). Results indicated that the ethanol, n-hexane, and n-butanol fractions exhibited no inhibitory effects on the tested microorganisms. In contrast, the ethyl acetate fraction displayed the highest level of antimicrobial activity (Staphylococcus aureus ATCC 6538, Pseudomonas aeruginosa ATCC 27853, and Candida albicans ATCC 1023). Further analysis of the ethyl acetate fraction revealed key bioactive compounds, including Coixol (phenol-group), Trigonelline and 2,6-Dimethyl quinoline (alkaloid-group), and Chebuloside-II (terpenoid-group). In summary, this pioneering research represents the first-ever exploration of the antimicrobial potential of cassava tubers, specifically focusing on the Sao Pedro Petro variety. The study not only underscores the antimicrobial properties of Manihot esculenta tubers but also identifies specific bioactive compounds within them, providing valuable insights into their potential therapeutic applications